2017
DOI: 10.1186/s12891-017-1596-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and time trends of distal forearm fractures in adults - a study of 11.2 million person-years in Sweden

Abstract: BackgroundA distal forearm fracture is a very common injury causing both suffering and substantial health care costs. The incidence of this fracture type seemed to increase worldwide until the middle 1980’s, but thereafter most reports have shown stable or decreasing rates. As few large studies have been presented lately we aimed to describe recent epidemiology and time trends of distal forearm fractures in adults. We paid special attention to fractures in working ages as they present challenges in terms of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 45 publications
5
56
1
4
Order By: Relevance
“…Our study compared the incidence of distal radius fracture over time in the same geographical region and used wrist radiographs to identify and verify fracture cases. Our results are in contrast to a register-based study from Skåne region in Sweden [24] that reported a significant increase in the incidence of distal forearm fracture from 1999 to 2010, in both men and women. Our results are also in contrast to a study from Taiwan that reported annual increase in the incidence of distal radius fracture between years 2000 and 2007 [25].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study compared the incidence of distal radius fracture over time in the same geographical region and used wrist radiographs to identify and verify fracture cases. Our results are in contrast to a register-based study from Skåne region in Sweden [24] that reported a significant increase in the incidence of distal forearm fracture from 1999 to 2010, in both men and women. Our results are also in contrast to a study from Taiwan that reported annual increase in the incidence of distal radius fracture between years 2000 and 2007 [25].…”
Section: Discussioncontrasting
confidence: 99%
“…In light of this, surgeons will be confronted with higher numbers of (low-energy-associated fractures due to age-related diseases like osteoporosis and accidental falls [4,5]. Especially, osteoporosis, with high prevalence in people over 50 years [6], causes typical fractures of the elderly affecting the proximal humerus, distal radius, proximal femur, ankle joint, spine and pelvis [7][8][9][10]. Treatment of these fractures and comorbidities respectively represents a challenge for the attending physician.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent fracture in adults is the distal radius fracture. The reported incidence rate in Southern Sweden is as high as 278 per 100,000 person years and increasing, especially among those of working age [1,2]. Although a distal radius fracture is often regarded as simple with good prognosis, a considerable number of individuals experience prolonged pain and disability [3].…”
Section: Introductionmentioning
confidence: 99%